Cyclosporine A Downregulates MMP-3 and MMP-13 Expression in Cultured Pterygium Fibroblasts. Issue 9 (September 2015) - Kim, Yeoun-Hee; Jung, Jae-Chang; Jung, Soon-Young; Kim, Yong Il; Lee, Kyoo Won; Park, Young Jeung
Abstract : Purpose: To investigate the regulation of matrix metalloproteinase (MMP)-3 and MMP-13 expression over time and in the presence of cyclosporine A (CsA) in primary cultured human pterygium fibroblasts. We also examined the effects of CsA on cultured human pterygium fibroblasts. Methods: Primary cultured human pterygium fibroblasts subjected to scratch assays were exposed to 1 and 100 µg/mL of CsA for 3 or 10 minutes. Cells were washed with Dulbecco phosphate-buffered saline, and then incubated with serum-depleted Dulbecco modified Eagle medium/F-12 medium for 48 hours. Expression levels of MMP-3 and MMP-13 proteins and the corresponding mRNA transcripts were determined by western blotting and reverse transcription polymerase chain reaction assays, respectively. Results: Migration of cultured pterygium fibroblast cells was suppressed by pretreatment with CsA compared with controls in a time-dependent and dose-dependent manner (3 minutes, 50.6% ± 1.1 in 1 µg/mL, 60.0% ± 1.2 in 100 µg/mL; 10 minutes, 59.8% ± 5.7 in 1 µg/mL, 60.5 ± 2.4 in 100 µg/mL, respectively, P < 0.01). Pretreatment with CsA also reduced the mRNA ( P < 0.05) and protein expression levels ( P < 0.05). Conclusions: CsA was actively involved in the migration of pterygium fibroblasts. Cell migration is inhibited in response to CsA through the inhibition of MMP-3 and MMP-13 expression. These findings reveal the therapeutic potential of CsA on pterygium progression. Further studies will be necessary to elucidate the precise intracellular signal mechanism responsible for CsA-induced downregulation of MMPs in pterygium fibroblasts.